(untitled) (Journal of Enam Medical College, 2012)
Background: Since antibiotic resistance of uropathogens has gradually been rising, knowledge of antimicrobial resistance pattern of Escherichia coli (Esch. coli), the predominant pathogen of urinary tract infection (UTI), is important in selecting empirical antimicrobial therapy. Objectives: To find out the common organisms causing UTI with their antimicrobial susceptibility pattern in Enam Medical College Hospital. Materials and Methods: This study was carried out in the department of Microbiology, Enam Medical College Hospital, Savar, Dhaka between January 2010 to June 2011 to see the antimicrobial resistance pattern of Esch. coli in urine sample. A total of 512 urine samples were studied from clinically suspected UTI cases irrespective of age and sex. Esch. coli were isolated and antibiogram of the isolates were done. Results: The results of antibiogram revealed the resistance pattern of the isolated Esch. coli to ampicillin (93.94%), cefradine (70.71%), trimethoprim-sulfamethoxazole (48.49%), azithromycin (41.42%), ciprofloxacin (39.40%), ceftazidime (35.56%), nitrofurantoin (29.30%), ceftriaxone (10.11%), gentamicin (7.08%) and imipenem (3.04%). Conclusion: It can be inferred that our findings will render useful information to clinicians in determining the appropriately directed antimicrobial regimen when given empirically. DOI: http://dx.doi.org/10.3329/jemc.v1i2.11463 J Enam Med Col 2011; 1(2): 60-62